2010
DOI: 10.1158/0008-5472.can-09-3567
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Adenovirus Coding for Granulocyte Macrophage Colony-Stimulating Factor Induces Antitumoral Immunity in Cancer Patients

Abstract: Granulocyte macrophage colony-stimulating factor (GMCSF) can mediate antitumor effects by recruiting natural killer cells and by induction of tumor-specific cytotoxic T-cells through antigen-presenting cells. Oncolytic tumor cell-killing can produce a potent costimulatory danger signal and release of tumor epitopes for antigen-presenting cell sampling. Therefore, an oncolytic adenovirus coding for GMCSF was engineered and shown to induce tumor-specific immunity in an immunocompetent syngeneic hamster model. Su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
262
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(276 citation statements)
references
References 48 publications
7
262
2
1
Order By: Relevance
“…It is generally thought that armed oncolytic viruses are more potent than unarmed viruses and therefore the former are typically employed in clinical development. 9,18,21,43 In conclusion, we have shown that oncolytic adenovirus can be used to improve the efficacy of adoptive TIL transfer. Also, this is the first time TIL of the Syrian hamster have been cultured, characterized and used therapeutically.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is generally thought that armed oncolytic viruses are more potent than unarmed viruses and therefore the former are typically employed in clinical development. 9,18,21,43 In conclusion, we have shown that oncolytic adenovirus can be used to improve the efficacy of adoptive TIL transfer. Also, this is the first time TIL of the Syrian hamster have been cultured, characterized and used therapeutically.…”
Section: Discussionmentioning
confidence: 81%
“…8 Several implantable tumor cell lines, with wide histological range, have been identified and utilized in cancer gene therapy studies with oncolytic adenovirus vectors in this fully immunocompetent model. 9,10 Yet, immunological studies of Syrian hamster tumors are scarce, owing to general lack of hamster-specific reagents. With regard to TIL therapy, the features and therapeutic potential of TIL in hamsters are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of studies have shown beneficial effects of antiangiogenic treatment in various cancer models. [66][67][68][69] The angiogenesis caused by oncolytic herpes viruses may have deleterious effects on the late phase of cancer therapy, especially with regard to late recurrences that occur after the end of the treatment regimen. In order to investigate this effect, we initiated a series of preclinical studies combining oncolytic herpes viruses with the monoclonal anti-VEGFA antibody bevacizumab in various cancer models.…”
Section: X400 X400mentioning
confidence: 99%
“…39 Also, we have demonstrated previously that oncolytic adenoviruses expressing immunomodulatory agents are able to induce tumor-specific immunity by triggering the innate and adaptive pathways of the immune system. 40,41 Of note, the oncolytic platform may be useful for increasing 'danger signals', useful for immunity versus tolerance.…”
Section: Discussionmentioning
confidence: 99%